A new medium-sized rupicolous Cnemaspis Strauch, 1887 (Squamata: Gekkonidae) of the C. bangara clade from granite boulder habitats in Krishnagiri, Tamil Nadu, India - Agarwal, Ishan; Thackeray, Tejas; Khandekar, Akshay (Zootaxa, 2021)
We describe a new species of the Cnemaspis bangara clade from a rocky hillock near Kugai Periya Mariamman Temple, Krishnagiri fort, Krishnagiri District of Tamil Nadu, India. Cnemaspis krishnagiriensis sp. nov. can be diagnosed from all other peninsular Indian congeners by its medium body size (maximum SVL 40 mm), heterogeneous dorsal pholidosis, spine-like tubercles absent on flanks; presence of four femoral pores on each thigh separated on either side by nine or 10 poreless scales from three continuous precloacal pores in males; tail with enlarged, strongly keeled, conical tubercles forming four whorls on anterior portion, six tubercles in first whorl, four tubercles in second to fourth whorls, enlarged tubercles restricted to only paravertebral region on rest of the tail; median row of sub-caudals smooth and distinctly enlarged, and a unique colour pattern. The new species can be diagnosed from members of C. bangara clade by the number of dorsal tubercles rows at mid-body, the number of enlarged tubercles in paravertebral rows, the number of ventral scales across belly at mid-body, the number longitudinal ventral scales from mental to cloaca, the number of femoral and precloacal pores and poreless scales separating these series, and subtle colour pattern differences; besides 9.2–17.6 % uncorrected ND2 sequence divergence. Cnemaspis krishnagiriensis sp. nov. is the fourth member of the recently described bangara clade and is the first that is known to be distributed <900 m asl.. The discovery of yet another endemic species of Cnemaspis from lower elevations of the Mysore Plateau once again highlights the need of dedicated systematic sampling to uncover the true diversity of Cnemaspis. We also address a nomenclatural issue related to the recently described Cnemaspis stellapulvis Khandekar, Thackeray & Agarwal.